Effect of Quercetin on Cadmium Chloride-Induced Impairments in Sexual Behaviour and Steroidogenesis in Male Wistar Rats - Ujah A.G, Nna U.V, Leku B.C.,Osim E.E. (Andrologia, 2017)
Cadmium chloride (CdCl2) has been reported to cause reproductive toxicity in male rats, mainly through oxidative stress. This study examined its effect on sexual behaviour, as one of the mechanisms of reproductive dysfunction, as well as the possible ameliorative effect of quercetin (QE) on same. Thirty male Wistar rats (10 weeks old), weighing 270–300 g, were used for this study. They were either orally administered 2% DMSO, CdCl2 (5 mg/kg b.w.), QE (20 mg/kg b.w.) or CdCl2+QE, once daily for 4 weeks, before sexual behavioural studies. The 5th group received CdCl2 for 4 weeks and allowed 4-week recovery period, before sexual behavioural test. Rats were sacrificed after sexual behavioural studies. The blood, testis and penis were collected for biochemical assays. Cadmium increased mount, intromission and ejaculatory latencies, but reduced their frequencies, compared to control. Serum nitric oxide increased, while penile cyclic guanosine monophosphate reduced in the CdCl2-exposed rats, compared to control. CdCl2 increased testicular cholesterol, but reduced 3β-hydroxysteroid dehydrogenase (3β-HSD) and 17β-HSD activities, and testosterone concentration. QE better attenuated these negative changes compared to withdrawal of CdCl2 treatment. In conclusion, CdCl2 suppressed steroidogenesis, penile erection and sexual behaviour, with poor reversal following withdrawal, while QE attenuated these effects.